Correlation of streamflow and sediment concentration at upstream and downstream Padang Watershed - Kemala Sari Lubis; Erwin Masrul Harahap; Abdul Rauf; Zainal Arifin Hasibuan (Syiah Kuala University, 2013)
Sediment concentration affected b streamflow at river body. This research was conducted to study correlation between streamflow and sediment concentration at upstream and downstream Padang watershed on July until December 2013. The research was conducted by using survey method at two outlet of Padang watershed were Padang sub watershed and Padang Hilir sub watershed. Sampling of water at two (2) outlets were conducted at stream surface by using depth intergrating suspended sediment sampler technique at three (3) points of river body. Sampling waters conducted at two times that were after rainand no rain. Sediment concentration (Cs) calculated by Cs = (G2 – G1) / V equation. Streamflow (Q) calculated by multiplying velocity and wide of river by Q = A x V equation. The results showed that no correlation between streamflow and sediment concentration at upstream when no rain (Cs = 0,0007 +0,0412 Q; R2 = 0,43) and at downstream when no rain (Cs = 0,0002 Q + 0,07157; R2 = 0,057). There were correlation between streamflow and sediment concentration at upstream after rain (Cs = 0,00041 Q +0,0611; R2 = 0,88) and at downstream after rain (Cs = 0,00015 Q + 0,03293; R2 = 0,9).